Blocking SphK/S1P/S1PR1 axis signaling pathway alleviates remifentanil-induced hyperalgesia in rats. (28th March 2023) - Li, Jie; Wang, Qian; Gao, Yangzheng; Ma, Wanjie; Sun, Zexian; Yu, Yonghao; Li, Yize; Li, Qing; Wang, Chunyan
Highlights: Remifentanil infusion induced increased expression of ceramide, sphingosine kinases (SphK) and sphingosine-1-phosphate (S1P) at protein level in the spinal. Sphingosine-1-phosphate receptor1 (S1PR1) is the mainly S1P receptor to mediate remifentanil-induced hyperalgesia. Blocking the SphK/S1P/S1PR1 axis could attenuate remifentanil-induced hyperalgesia and the expression of the NOD-like receptor protein 3 (NLRP3) related protein. As a downstream signaling pathway of SphK/S1P/S1PR1 axis, reactive oxygen species (ROS) pathway was involved in the remifentanil-induced hyperalgesia. Abstract: Recent research shows a correlation between altered sphingolipid metabolism and nociceptive processing. Activation of the sphingosine-1-phosphate receptor 1 subtype (S1PR1) by its ligand, sphingosine-1-phosphate (S1P), causes neuropathic pain. However, its role in remifentanil-induced hyperalgesia (RIH) has not been investigated. The purpose of this research was to establish if the SphK/S1P/S1PR1 axis mediated remifentanil-induced hyperalgesia and identify its potential targets. This study examined the protein expression of ceramide, sphingosine kinases (SphK), S1P, and S1PR1 in the spinal cord of rats treated with remifentanil (1.0 μg/kg/min for 60 min). Prior to receiving remifentanil, rats were injected with SK-1 (a SphK inhibitor); LT1002 (a S1P monoclonal antibody); CYM‐5442, FTY720, and TASP0277308（the S1PR1 antagonists); CYM-5478 (a S1PR2 agonist); CAY10444 (a S1PR3 antagonist); Ac-YVAD-CMK (a caspase-1 antagonist); MCC950 (the NOD-like receptor protein 3 (NLRP3) inflammasome antagonist); and N - tert -Butyl-α-phenylnitrone (PBN, a reactive oxygen species (ROS) scavenger). Mechanical and thermal hyperalgesia were evaluated at baseline (24 h prior to remifentanil infusion) and 2, 6, 12, and 24 h following remifentanil administration. The expression of the NLRP3-related protein (NLRP3, caspase-1), pro-inflammatory cytokines (interleukin-1β(IL-1β), IL-18), and ROS was found in the spinal dorsal horns. In the meantime, immunofluorescence was used to ascertain if S1PR1 co-localizes with astrocytes. Remifentanil infusion induced considerable hyperalgesia in addition to increased ceramide, SphK, S1P, and S1PR1, NLRP3-related protein (NLRP3, Caspase-1, IL-1β, IL-18) and ROS expression, and S1PR1 localized astrocytes. By blocking the SphK/S1P/S1PR1 axis, remifentanil-induced hyperalgesia was reduced, as was the expression of NLRP3, caspase-1, pro-inflammatory cytokines (IL-1β, IL-18) and ROS in the spinal cord. In addition, we observed that suppressing NLRP3 or ROS signal attenuated the mechanical and thermal hyperalgesia induced by remifentanil. Our findings indicate that the SphK/SIP/S1PR1 axis regulates the expression of NLRP3, Caspase-1, IL-1β, IL-18 and ROS in the spinal dorsal horn to mediate remifentanil-induced hyperalgesia. These findings may contribute to pain and SphK/S1P/S1PR1 axis research positively, and inform the future study of this commonly used analgesic.